Combination of cervical cancer and unilateral complete aplasia of the adnexa: a case report - A. L. Chernyshova; L. A. Kolomiets; A. Yu. Kishkina; М. O. Ochirov (Бюллетень сибирской медицины, 2019)
We  present  a  rare  case  of  the  combination   of  cervical  cancer  and  unilateral complete   aplasia  of  the uterine  adnexa.    Female  genital  tract anomalies  account  for  about  4% of all congenital  malformations.Congenital  malformations  of the  adnexa  are  very  rare,  accounting  for  less than  0.5%. In  the  presented case, this abnormality was found incidentally during surgery for cervical cancer. Medical genetic counseling confirmed  the presence  of the isolated congenital  pathology.